Oceanic acidification affects marine carbon pump and triggers extended marine oxygen holes - Hofmann, Matthias (National Academy of Sciences, 2009)
Rising atmospheric CO(2) levels will not only drive future global mean temperatures toward values unprecedented during the whole Quaternary but will also lead to massive acidification of sea water. This constitutes by itself an anthropogenic planetary-scale perturbation that could significantly modify oceanic biogeochemical fluxes and severely damage marine biota. As a step toward the quantification of such potential impacts, we present here a simulation-model-based assessment of the respective consequences of a business-as-usual fossil-fuel-burning scenario where a total of 4,075 Petagrams of carbon is released into the atmosphere during the current millennium. In our scenario, the atmospheric pCO(2) level peaks at ≈1,750 μatm in the year 2200 while the sea-surface pH value drops by >0.7 units on global average, inhibiting the growth of marine calcifying organisms. The study focuses on quantifying 3 major concomitant effects. The first one is a significant (climate-stabilizing) negative feedback on rising pCO(2) levels as caused by the attenuation of biogenic calcification. The second one is related to the biological carbon pump. Because mineral ballast, notably CaCO(3), is found to play a dominant role in carrying organic matter through the water column, a reduction of its export fluxes weakens the strength of the biological carbon pump. There is, however, a third effect with severe consequences: Because organic matter is oxidized in shallow waters when mineral-ballast fluxes weaken, oxygen holes (hypoxic zones) start to expand considerably in the oceans in our model world—with potentially harmful impacts on a variety of marine ecosystems.